PERBANDINGAN METODE EKSTRAKSI TERHADAP RENDEMEN EKSTRAK DAUN RAMBAI LAUT (Sonneratia caseolaris L. Engl) - Heri Wijaya; Novitasari Novitasari; Siti Jubaidah (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Rambai laut (Sonneratia caseolaris L. Engl) is one of the typical plants of Borneo that the leaves are empirically used by the community as a medicinal plant. Compounds from plants can be obtained by extraction. The yield rendement on the extraction process can be influenced by several factors, one of which is the method of extraction. This study aims to determine the effect of extraction methods and the amount of yield produced on rambai laut extracts. The research design is experimental with descriptive analysis. Rambai laut which has become powder then in extraction by using maseration method, infundation method, reflux method and soxhletasi method. The result of rendement is then analyzed using statistic. Soxhletasi method yield average value of rendemen that is equal to 28,38%, reflux equal to 25,57%, maseration equal to 21,28% and infundasi with average value of rendemen that is equal to 17,20%. The soxhletation method yields the highest average yield value and infundation with the lowest average yield value. The result of staitistic test shows that the extraction method has an effect on each rendement with p value = 0,024 <α = 0,05. Keywords : Sonneratia caseolaris, extraction method, rendement